Evidence for Rapoport's rule and latitudinal patterns in the global distribution and diversity of alien bird species. (3rd March 2020) - Dyer, Ellie E.; Redding, David W.; Cassey, Phillip; Collen, Ben; Blackburn, Tim M.
Abstract: Aim: To quantify global latitudinal patterns in the distributions of alien bird species to assess whether these species conform to Rapoport's rule (i.e. show a positive latitudinal gradient in latitudinal range extent), and to test whether where species are introduced, and where species fail to establish, may help to drive observed patterns. Location: Global. Taxon: Birds (group Aves). Methods: Data on locations of introduction and establishment for 355 species with established alien populations were combined with data on native range extents (measured in 5° bands of latitude). Relationships between (a) latitude and introduced and established alien species richness, and (b) latitude and introduced and established alien range extent, were plotted. Linear regressions and paired t ‐tests were used to compare latitudinal range extents, midpoints, and limits of each species in its introduced alien range, established alien range and native range. Results: Latitudes that have more established alien bird species also have had more species introduced in total. The mean total latitudinal extents (i.e. geographic range size) of established alien bird species increase with latitude poleward of the tropics, consistent with Rapoport's rule, but are smaller in the tropics. This pattern is weaker in the range sizes of native bird species. Alien bird species are more likely to be introduced within the latitudinal confines of their native ranges, and are more likely to contract away from the more extreme latitudes to which they were introduced. Alien bird species are in general more likely to have established populations nearer the equator. Main conclusions: Including data on locations of introduction in addition to established distributions enables us to determine the extent to which large‐scale alien species distributions are determined by anthropogenic or natural processes. Latitudinal patterns in range extent (Rapoport's rule) and species richness in alien birds are largely a consequence of where species have been introduced, and hence are unlikely to be informative of equivalent patterns in native species.